RIMA DAN ENJAMBEMEN PUISI DALAM KUMPULAN PUISI DUKAMU ABADI KARYA SAPARDI DJOKO DAMONO - Suwardo, F.X. (Universitas Katolik Widya Mandala Surabaya Kampus Kota Madiun, 2012)
This study was designed to find and explain particular aspects of the elements of rhymes and enjambemen of poem as well as its influence on beauty. Therefore, the most appropriate method applied here is descriptive-qualitative research. The result of the research on poems indicated that there were various types of rhymes. The analysis of the sounds of rhymes showed that all of the samples (24 poems) made use of imperfect rhymes. While, the analysis of the locations of rhymes in lines found both initial and final rhymes. The initial rhymes were found in 4 poems; while, the final rhymes were found in all of the samples. The analysis of locations of rhymes in temples found some crossed rhyme (a-b-a-b), continuous rhyme (a-a-a-a), paired rhyme (a-a-b-b), and broken rhyme (a-a-a-b). Those rhymes were found in one poem all together. In other words, the crossed, continuous, and paired rhymes were found in one poem, or the continuous, broken, and paired rhymes were found in one poem. The analysis of the use of enjambemen events indicated that 12 poems used enjambemen. Enjambemen events were functionally used by poets. It means that they were used appropriately not only to create the beauty of poem but also to reinforce its meaning and nuance.